Do Dictionary Users Really Look Up Frequent Words? — On the Overestimation of the Value of Corpus-based Lexicography - de Schryver, Gilles-Maurice; Joffe, David; Joffe, Pitta; Hillewaert, Sarah (Lexikos, 2006)
Abstract: An innovative online Swahili–English dictionary project is presented. A careful study of some of the log files attached to this reference work reveals some hitherto unknown as-pects of true dictionary look-up behaviour, which results in the depreciation of the importance of corpora for dictionary making. Three lexicography software modules are advanced to further enhance the success of the online dictionary.Keywords: LEXICOGRAPHY, SOFTWARE, ONLINE, DICTIONARY, LOG FILE, CORPUS, FREQUENCY, RANK, CORRELATION, SWAHILI, ENGLISH, TSHWANELEXSamenvatting: Zoeken woordenboekgebruikers werkelijk frequente woor-den op? — Over de overschatting van de waarde van corpusgebaseerde lexi-cografie. Een vernieuwend online Swahili–Engels woordenboekproject wordt voorgesteld. Een minutieuze studie van enkele van de log bestanden gekoppeld aan dit referentiewerk onthult tot dusver onbekende aspecten van het echte opzoekgedrag van woordenboekgebruikers, wat leidt tot een devaluatie van het belang van corpora voor het maken van woordenboeken. Drie lexicogra-fische softwaremodules worden naar voor geschoven om het succes van het online woordenboek verder te vergroten.Sleutelwoorden: LEXICOGRAFIE, SOFTWARE, ONLINE, WOORDENBOEK, LOG BE-STAND, CORPUS, FREQUENTIE, RANG, CORRELATIE, SWAHILI, ENGELS, TSHWANELEX